Evaluation of the CIPP Model in the Tax Administration Core System Business Process E-learning Program at the Tax Education and Training Center - Yudi Ristu Prihawan; Sugeng Bayu Wahyono (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study evaluates the SIAP Core Tax Administration System Business Process E-learning Program delivered by the Tax Training Center, Ministry of Finance, Indonesia, using the CIPP model (Context, Input, Process, Product). The evaluation examines alignment with organizational needs, resource readiness, implementation quality, and impacts on participants’ performance and their work units within the Directorate General of Taxes’ digital transformation agenda. A descriptive quantitative design was applied at the Tax Training Center and the Directorate General of Taxes (Special Region Jakarta). Participants were program alumni. Data were collected through a CIPP-based questionnaire and complemented by interviews with e-learning managers, with triangulation supported by relevant documents. Quantitative data were analyzed using descriptive statistics, while interview findings were used to enrich interpretation. Results indicate that the program is rated very good across all CIPP components: the context shows clear needs-based design and policy support; inputs reflect adequate instructors, learning materials, and facilities; the process demonstrates structured delivery with interactive elements; and the product reveals positive effects on participants’ competence and job performance. The study recommends continuous improvement and periodic evaluation of the program to strengthen human resource capacity for SIAP implementation.